2019
DOI: 10.1609/icwsm.v13i01.3353
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure of Bullying Experiences and Social Support in Avatar Communication: Analysis of Verbal and Nonverbal Communications

Abstract: Avatar communication through the Internet has great potential to be an appropriate environment for self-disclosure and social support. Anonymity and ease of access drive selfdisclosure of even the most serious problems. Rich nonverbal communication, co-presence, and real-time interaction increase emotional closeness. However, there has not been much research with regard to examining social support in avatar communication. In this paper, we aim to facilitate self-disclosure and social support for bullied people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Online social support can complement offline social support (Trepte et al 2015;Cole et al 2017). Particularly, this is effective for people who lack social resources (Mesch and Talmud 2006;Chung 2013;Yokotani and Takano 2021a;Pierce et al 2020), including bullying victims (Cole et al 2017;Takano and Tsunoda 2019). One reason is anonymity.…”
Section: Related Work Online Social Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…Online social support can complement offline social support (Trepte et al 2015;Cole et al 2017). Particularly, this is effective for people who lack social resources (Mesch and Talmud 2006;Chung 2013;Yokotani and Takano 2021a;Pierce et al 2020), including bullying victims (Cole et al 2017;Takano and Tsunoda 2019). One reason is anonymity.…”
Section: Related Work Online Social Supportmentioning
confidence: 99%
“…One reason is anonymity. While not all social platforms have anonymity as the default feature (e.g., Facebook), previous studies showed that those that do promotes self-disclosure of negative experiences (Kang et al 2016) (e.g., sexual abuse (Andalibi et al 2016) and bullying victimization (Cole et al 2017;Takano and Tsunoda 2019)), which are difficult in offline relationships because of the fear of rejection by listeners (Mesch and Talmud 2006;Andalibi et al 2016).…”
Section: Related Work Online Social Supportmentioning
confidence: 99%
See 3 more Smart Citations